2013
DOI: 10.1016/s0924-9338(13)77482-0
|View full text |Cite
|
Sign up to set email alerts
|

2942 – Anxiety and depression among parents of children with mental retardation

Abstract: Background:Studies have shown an association between parental anxiety and depression, and caretaking of children with developmental cognitive delays. There is little data in developing countries, such as Pakistan, concerning the impact of raising children with Mental Retardation, upon the quality of parent functioning and risk for psychopathology.Objective:To evaluate for anxiety and depression among parents of children with Mental Retardation (MR).Methods:This was a prospective study conducted at a tertiary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…After parents read the parenting module for parents of children with mental retardation, parents get knowledge. After gaining knowledge about caring for children with mental retardation, parents can understand children with mental retardation where understanding is defined as the ability to understand the material being studied (Dogar et al, 2013;Istafia et al, 2020;Kosasih, 2017). At this level, parents can provide examples of both principles and concepts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After parents read the parenting module for parents of children with mental retardation, parents get knowledge. After gaining knowledge about caring for children with mental retardation, parents can understand children with mental retardation where understanding is defined as the ability to understand the material being studied (Dogar et al, 2013;Istafia et al, 2020;Kosasih, 2017). At this level, parents can provide examples of both principles and concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Parents of children with mental retardation experience stages of psychological conditions such as shock, rejection, guilt, anger, frustration and depression (Hadjimina & Furnham, 2017;Jalali et al, 2016). Several studies have shown that parents of children with mental retardation show feelings of sadness, depression, anger and lack of acceptance of their child's condition (Dogar et al, 2011(Dogar et al, , 2013. They feel that their children are not developing like other children at their age, parents are worried about their children's future and the stigma attached to their children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Despite the tremendous progress in field of cardiology, majority of this growing population with CHD even after the surgery continue to face life-long challenges and are at risk for having a poor (QOL). 8 QOL is a broader term and it seems to depend on multiple factors, good health is directly related to it. In children with CHD to a limited extent the QOL is mainly determined by their heart defect, both palliative and corrective surgery always aims to improve QOL.…”
Section: Introductionmentioning
confidence: 99%